THE FOREIGN POLICY OF THE UNITED STATES: LEADING POWER? - De Alba-Ulloa, Jessica (The Copernicus Journal of Political Studies, 2018)
The United States, with its historical background of exceptionalism, rose to power in the twentieth century and has maintained it until today. If it were not for the state’s economic power and its strong institutions within the three branches of government, the U.S. would not be now a dominant global power and a regional hegemonic leader. Thus, even when faced with the lack of leadership, the state is able to retain its dominance in the international arena. Supported with a short review of U.S. history, this article presents the state’s (in)activism in global politics during Obama’s presidency.